Preparing Tomorrow’s Teachers to Use Technology (PT3) at Boston University through Faculty Development - David Whittier; Sonia Lara (Estudios sobre Educación, 2018)
Boston University School of Education received a grant for Preparing Tomorrow’s Teachers to use Technology from U.S. Department of Education. The project focused on faculty development in learning the Web and digital tools and reflecting on technology’s value for teacher preparation. Qualitative data showed gains in understanding and using technology but little radically new pedagogy. Trained educational technologists facilitated faculty learning and production. Recommendations include: learn by doing; provide “just in time” expert help; focus on the pedagogical advantages of technology, not on technology itself, and use formative evaluation to guide planning. The project proposes to sustain faculty’s new skills in developing a web-based curriculum.